Effect of nonylphenol on the colonic mucosa in rats and intervention with zinc-selenium green tea (Camellia sinensis). Issue 1 (29th December 2021) - Li, Shixu; Zheng, Mucong; Yang, Xuefeng; Zhang, Jianling; Xu, Jie; Yu, Jie
Abstract: To investigate the effect of nonylphenol (NP) exposure on the colonic mucosa in rats, and the protective effects of Guizhou zinc-selenium tea (Zn-Se tea) on the damage induced by NP, sixty Sprague–Dawley rats were randomly divided into 6 groups ( n = 10 in each group): control group (corn oil), and rats gavaged with NP at the doses of 0.4 mg/kg/d (Low NP group), 4 mg/kg/d (Medium NP group), 40 mg/kg/d (High NP group), and 40 mg/kg NP combined with green tea group at the doses of 0.2 g/ml (NP + GT group) and 0.2 g/ml Zn-Se tea group (NP + ZST group). NP at 40 mg/kg/d was administered to the tea groups for 3 months, followed by NP + green tea and NP + Zn-Se tea for 4 months, and the rest of the groups were gavaged for 7 months. With the increase of NP concentration, NP accumulation in colon gradually increased ( P < 0.05), colonic villi shortened, tight junctions between cells widened, intestinal integrity was impaired, and goblet cells, intraepithelial lymphocytes and mast cells were significantly lower in NP high-dose group than in control group ( P < 0.05). Meanwhile, the protein expression of Caspase-1, IL-1β and Pro-IL-1β in NP high-dose group was significantly higher than that in control group ( P < 0.05). Zn-Se tea increased the number of goblet cells in colon and decreased the accumulation of NP in colon ( P < 0.05); Zn-Se tea and common green tea decreased the expression of Caspase-1 and Pro-IL-1β protein ( P < 0.05). NP exposure can destroy intestinal morphology, reduce the number of intestinal immune cells, reduce intestinal immunity and increase the release of inflammatory factors; Guizhou Zn-Se tea has a certain protective effect on colon damage caused by NP.